Marketing Strategy Analysis Of Health Services For Bpjs Participants At Aliyah 2 Hospital Kendari City - Nurdin, Ishmah Farah Adiba; Sulistiyowati, Yeny; Aminingsih, Purwanti; Agustin, Dinni (Journal of Ageing And Family, 2024)
Background: Aliyah 2 Hospital in Kendari City faces challenges in improving BPJS services amidst competition, so marketing strategies are key to improving service quality, patient satisfaction, and competitiveness. Objective: This study aims to analyze the marketing strategies implemented by Aliyah 2 Hospital in improving health services for BPJS participants, and to identify factors that influence its success. Method: This study uses a mixed-method with quantitative data from BPJS patient questionnaires and qualitative data from interviews with management and marketing staff. The analysis was conducted using SPSS 26 through validity, reliability, and multiple linear regression tests. Results: Marketing strategies such as social media, service promotion, and improving service quality have a positive impact on BPJS patient satisfaction and visits, although they are still constrained by budget, experts, and service convenience. Conclusion: The conclusion of this study is that an effective marketing strategy can improve the hospital's competitiveness in providing services to BPJS participants. Recommendations provided include improving digital marketing strategies, optimizing technology-based services, and strengthening relationships with patients through the Customer Relationship Management (CRM) program. Keywords: Marketing strategy, health services, BPJS, patient satisfaction, hospital.